(untitled) (Bangladesh Journal of Botany, 2021)
A field experiment was carried out to screen low phosphorus tolerance indexes in common bean. Analysis and comparison of the coefficient of variation of the relative values of phosphorus efficiency-related indexes in 30 common bean varieties subjected to different phosphorus treatments were identified. Plant dry matter weight, phosphorus accumulation, and acid phosphatase activity are important indexes for determining low-phosphorus tolerance. A comprehensive evaluation system for low-phosphorus tolerance in common bean was established using the fuzzy membership function method. Varieties with a composite index ≥ 0.49 were identified as low phosphorus tolerant varieties, including “Longyun 13,” “Longyun 6,” and “Long17- 3525,” while varieties with a composite index ≤ 0.27 were identified as varieties sensitive to low phosphorus, including “Long12-2752,” “NR,” and “Long15-1554.” Bangladesh J. Bot. 50(3): 903-909, 2021 (September) Special